An analysis of the constitutionality of the President's reliance on 'prerogative powers' as the basis for appointing or dismissing cabinet members - an interrogation of the meaning of section 91(2) of the Constitution - Malan, Jacobus J. (Koos) (University of Pretoria, 2019)
Mini Dissertation (LLM)--University of Pretoria, 2018.